Building Corruption-Resilient Public Organizations Through Bureaucratic Professionalism, Digital Oversight Systems, Ethical Governance, and Whistleblowing Culture as Mediating Mechanisms - Muhammad Reza (Asosiasi Dosen Muda Indonesia, 2026)
Corruption remains one of the most persistent governance problems affecting public institutions worldwide, particularly in developing countries. Corrupt practices weaken institutional legitimacy, reduce public trust, damage economic development, and obstruct sustainable governance reform. This study aims to analyze strategies for building corruption-resilient public organizations through bureaucratic professionalism, digital oversight systems, ethical governance, and whistleblowing culture as mediating mechanisms. The study adopts a systematic literature review approach by analyzing peer-reviewed international and national journal articles published between 2015 and 2026. A total of 15 highly relevant journal articles were critically reviewed using thematic analysis, comparative analysis, and synthesis methods. The findings reveal that bureaucratic professionalism significantly contributes to corruption prevention through merit-based recruitment, competence development, institutional accountability, and procedural discipline. Digital oversight systems strengthen transparency, monitoring effectiveness, audit efficiency, and public participation in detecting corruption risks. Ethical governance enhances organizational integrity by promoting ethical leadership, institutional fairness, accountability mechanisms, and anti-corruption values. Furthermore, whistleblowing culture emerges as an important mediating mechanism capable of strengthening the relationship between organizational governance systems and corruption prevention effectiveness. The literature review demonstrates that organizations possessing strong professional bureaucracy, integrated digital supervision systems, ethical institutional cultures, and protected whistleblowing mechanisms tend to demonstrate higher corruption resistance and stronger public accountability. However, several studies indicate persistent obstacles including political intervention, weak legal protection, organizational resistance, technological limitations, fear of retaliation, and inadequate institutional commitment. This study contributes theoretically by integrating Institutional Theory, Good Governance Theory, Organizational Ethics Theory, and Fraud Triangle Theory in explaining corruption prevention systems within public organizations. Practically, the findings provide strategic recommendations for policymakers, public administrators, and anti-corruption institutions in strengthening sustainable anti-corruption governance systems.